The Influence of Gadgets on Menstruation of Medical student in Indonesia - Nurul Azizah; Hamsah, Muhammad; Novriansyah, Zulfikri Khalil; Kartika K, Irna Diyana; Arfah, Arni Isnaini (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2023)
Background: Menstruation is bleeding that comes out of the vagina periodically and cyclically in the corpus uteri accompanied by progestational endometrial desquamation as a sign of the process of maturity of the reproductive organs and fertility in women. Not all women have normal periods. Menstrual disorders are one of the gynecological problems affecting women of childbearing age with a global prevalence of 30-70%. In Indonesia, as many as 13.7% of 68% of women experience irregular menstruation, and 30% of women experience changes in menstrual patterns. The increasing prevalence of gadget use globally with a high level of mass media exposure results in disruption of menstruation supported by various factors. Aim: Identify and measure the influence of gadgets on menstrual disorders. Method: Probability proportional to size sampling through the provision of questionnaires with certain criteria to all female students of the class of 2020, then from 200 samples, research subjects who met the inclusion criteria were obtained as many as 134 people. Results: The highest duration of gadget use is 9-16 hours / day (weight) while menstrual symptoms (p = 0.876), length of menstrual days (p = 0.891), menstrual rhythm (p = 0.849), and menstrual distance to the next period (p = 0.651) so there is no significant relationship between the use of gadgets and the menstruation of female students. Conclusion: There was no significant relationship between the duration of gadget use and the menstruation of female students.